Edukasi Pola Hidup Sehat dan Bersih di SDN 6 Kwandang Kabupaten Gorontalo Utara - Trifandi Lasalewo; Herinda Mardin; Hariana Hariana (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
The importance of maintaining the fitness and health of elementary school age students as well as the cleanliness of the school environment has become a habit and a healthy and clean lifestyle. For this reason, healthy gymnastics activities and cleaning the school environment are carried out in order to provide education on healthy and clean lifestyles to students at SDN 6 Kwandang, North Gorontalo Regency. The method used in this activity is a participatory method and the participants who take part in the education activities for a healthy and clean lifestyle are all students of SDN 6 Kwandang and several communities around the school. The activity was carried out 2 (two) times during October 2021. The result of the education activity on a healthy and clean lifestyle is that the activity runs smoothly without significant obstacles. This can be seen from the enthusiasm of the participants and the community around the school who participated in healthy gymnastics and cleaning the environment around the school. Healthy gymnastics activities and cleaning the environment around the school have a positive impact, especially in terms of education, increasing awareness of maintaining physical fitness and cleaning the environment around the school for students and the surrounding community.